2013
DOI: 10.1016/j.bbmt.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparing High and Low Total Body Irradiation Dose Rates for Minimum-Intensity Conditioning of Dogs for Dog Leukocyte Antigen–Identical Bone Marrow Grafts

Abstract: We tested the hypothesis that total body irradiation (TBI) given at a high dose rate would be more immunosuppressive and lead to a higher incidence of stable hematopoietic cell engraftment following suboptimal levels of conditioning irradiation than irradiation given at a low dose rate. We assessed engraftment success of dog leukocyte antigen identical marrow transplantation into recipients given 100, 150, and 200 cGy TBI, administered at 7 or 70 cGy/min. Dogs received donor marrow the same day as TBI and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In the present study, radiation dose was identified as the most influential risk factor in graft rejection. In agreement with our data, previous preclinical studies have shown a significant association between nonmyeloablative radiation dose and the stability of engraftment [22][23][24]. Furthermore, some clinical studies in humans have described an increased risk of graft rejection in patients receiving nonmyeloablative conditioning compared with patients treated with a RIC regimen [25]; however, another clinical investigation failed to demonstrate an association between conditioning intensity and rejection rate in the nonmyeloablative/RIC HSCT setting [26].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, radiation dose was identified as the most influential risk factor in graft rejection. In agreement with our data, previous preclinical studies have shown a significant association between nonmyeloablative radiation dose and the stability of engraftment [22][23][24]. Furthermore, some clinical studies in humans have described an increased risk of graft rejection in patients receiving nonmyeloablative conditioning compared with patients treated with a RIC regimen [25]; however, another clinical investigation failed to demonstrate an association between conditioning intensity and rejection rate in the nonmyeloablative/RIC HSCT setting [26].…”
Section: Discussionsupporting
confidence: 90%
“…6,7 In addition, naturally occurring cancers in dogs often closely mimic human disease and offer a novel platform to study immunotherapies. Among canine malignancies, osteosarcoma (OS) has a high incidence, affecting roughly 8,000 dogs per year in the US.…”
Section: Introductionmentioning
confidence: 99%
“…For larger patients, an approximately 20 cm distance from the body wall to the beam spoiler was estimated, and it reached approximately 30 cm for smaller patients. Since normal dog TBI studies have been performed on awake dogs with no bolus material or beam spoiler and dosimetry data for these patients has not been published, we felt that the use of the beam spoiler was a reasonable choice to attempt to improve skin and buildup region dose homogeneity and decrease setup time. In this study, skin dose ranged from 94% to 104% and 87% to 118% of the planned dose in cadaver and patient dogs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of high‐dose TBI is replete with challenges. It is common to deliver treatment in multiple fractions and at low dose rates, in order to minimize risk of severe normal tissue injury . This can be accomplished with use of a special low dose rate package that is available on some linear accelerators.…”
Section: Introductionmentioning
confidence: 99%